2021
DOI: 10.15700/saje.v41n2a1855
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of learners with dyslexia in mainstream primary schools: An investigation

Abstract: With this study we sought to investigate the effectiveness of assessment of learners with dyslexia in mainstream primary schools in the Bubi district of Matabeleland North, Zimbabwe. An exploratory case study design of the qualitative approach was adopted. Semi-structured individual interviews and focus group interviews (FGI) were used to collect data from heads of schools and teachers selected for the study. Gathered data were analysed and interpreted thematically. The major findings of the study were that no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The findings concluded that most reading materials were not linked to learners' reading levels. This contradicts literature which states that the reading text must be carefully selected so that the learners are not frustrated by reading material that is more difficult than their abilities (Dulude, 2012;Nkomo et al, 2021) The questionnaire statement solicited the views of respondents regarding the adequacy of time that was allocated for the administration of intervention programmes for learners with dyslexia. 53 (35.3%) respondents strongly disagreed to the notion, and 64 (42.7%) disagreed, bringing the sum of those on the negative side to 117 (78%).…”
Section: Match Between Reading Materials and Academic Levels Of Learnersmentioning
confidence: 94%
See 1 more Smart Citation
“…The findings concluded that most reading materials were not linked to learners' reading levels. This contradicts literature which states that the reading text must be carefully selected so that the learners are not frustrated by reading material that is more difficult than their abilities (Dulude, 2012;Nkomo et al, 2021) The questionnaire statement solicited the views of respondents regarding the adequacy of time that was allocated for the administration of intervention programmes for learners with dyslexia. 53 (35.3%) respondents strongly disagreed to the notion, and 64 (42.7%) disagreed, bringing the sum of those on the negative side to 117 (78%).…”
Section: Match Between Reading Materials and Academic Levels Of Learnersmentioning
confidence: 94%
“…mapping of letter sounds and their spelling, the temporal lobe is where verbal memory resides, and the occipital lobe is known as the home of the visual cortex (Nkomo, Mulaudzi & Dube, 2021).…”
mentioning
confidence: 99%